2015
DOI: 10.1063/1.4905638
|View full text |Cite
|
Sign up to set email alerts
|

Laser-driven ion acceleration with hollow laser beams

Abstract: The laser-driven acceleration of protons from thin foils irradiated by hollow high-intensity laser beams in the regime of target normal sheath acceleration (TNSA) is reported for the first time. The use of hollow beams aims at reducing the initial emission solid angle of the TNSA source, due to a flattening of the electron sheath at the target rear side. The experiments were conducted at the PHELIX laser facility at the GSI Helmholtzzentrum für Schwerionenforschung GmbH with laser intensities in the range from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 16 publications
1
43
0
Order By: Relevance
“…Raman backscattering has been investigated in the frame of onedimensional physical models [23,24], focusing on energy flows between the intervening waves. As an application, we recently showed that Raman backscattering can amplify seed pulses with a single OAM level to the required intensities to explore relativistic laser-plasma interactions [21,[25][26][27]]-by using a counter-propagating long pump laser that also contains a single OAM mode [28]. Here we demonstrate that three-wave interactions can also be used to manipulate, with an unprecedented degree of controllability, the three-dimensional spatial-temporal laser pulse structure.…”
mentioning
confidence: 99%
“…Raman backscattering has been investigated in the frame of onedimensional physical models [23,24], focusing on energy flows between the intervening waves. As an application, we recently showed that Raman backscattering can amplify seed pulses with a single OAM level to the required intensities to explore relativistic laser-plasma interactions [21,[25][26][27]]-by using a counter-propagating long pump laser that also contains a single OAM mode [28]. Here we demonstrate that three-wave interactions can also be used to manipulate, with an unprecedented degree of controllability, the three-dimensional spatial-temporal laser pulse structure.…”
mentioning
confidence: 99%
“…In this paper, the generation of hot electrons at grazing incidence of a subpicosecond intense laser pulse onto a plane solid target is analyzed for the parameters of the petawatt high-energy laser for heavy ion experiments (PHELIX) (Bagnoud et al, 2010;Wagner et al, 2014a) using three-dimensional (3D) particle-in-cell (PIC) modeling (Pukhov, 1999) and a wide-range hydro modeling (Povarnitsyn et al, 2012a) of the preplasma expansion under the action of the laser prepulse. Elaboration of wide-range models of the laser-matter interaction is necessary for planning and interpretation of experiments carried out in view of different applications aimed for the development of secondary sources of high energy particles and hard radiation (Morace et al, 2014;Brabetz et al, 2015;Rusby et al, 2015;Vaisseau et al, 2015). Surface acceleration and transport of energetic electrons in intense laser-matter interactions at the grazing incidence were investigated experimentally for femtosecond laser pulses of hundreds mJ energy in (Wang et al, 2013;Mao et al, 2015) and for hundred joule subpicosecond laser pulses of the laser system PHELIX in paper (Gray et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another application of the annular laser pulses is the laserdriven acceleration of protons from thin foils irradiated by hollow high-intensity laser beams in the regime of target normal sheath acceleration (TNSA) (Brabetz et al, 2015). In this case, the use of annular beams aims at reducing the initial emission solid angle of the TNSA source (Brambrink et al, 2006;Yu et al, 2013), due to a flattening of the electron sheath at the target rear side.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the use of annular beams aims at reducing the initial emission solid angle of the TNSA source (Brambrink et al, 2006;Yu et al, 2013), due to a flattening of the electron sheath at the target rear side.…”
Section: Introductionmentioning
confidence: 99%